2020
DOI: 10.1001/jamanetworkopen.2020.22302
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Telehealth Utilization in the United States

Abstract: Key Points Question What is the prevalence of telehealth use in the US, and what demographic characteristics are associated with it? Findings This survey study of 2555 US adult respondents in an internet-based representative panel about use of telehealth found that only approximately 4% of participants had engaged in videoconferencing visits. While 49% of respondents expressed interest in using videoconferencing in the future, those who were older, identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
114
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 158 publications
(127 citation statements)
references
References 7 publications
10
114
3
Order By: Relevance
“…Our study indicates that Blacks are more likely to use and access telemedicine during the COVID-19 pandemic than other races, which can show how telemedicine can be a vital opportunity to reduce disparities. Previous study discuss that Blacks were more likely to report they did not know how to use videoconferencing visits (10). Although the mechanism of this study cannot confirm this contradiction, this difference can be due to the type of telehealth or diseases.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Our study indicates that Blacks are more likely to use and access telemedicine during the COVID-19 pandemic than other races, which can show how telemedicine can be a vital opportunity to reduce disparities. Previous study discuss that Blacks were more likely to report they did not know how to use videoconferencing visits (10). Although the mechanism of this study cannot confirm this contradiction, this difference can be due to the type of telehealth or diseases.…”
Section: Discussioncontrasting
confidence: 60%
“…The copyright holder for this preprint this version posted March 2, 2021. ; https://doi.org/10.1101/2021.03.01.21252330 doi: medRxiv preprint because they are disproportionately affected by multiple chronic diseases (9). A recent study in 2020 indicates that half of the sample were willing to use videoconferencing visits, and individuals who were older than 65 years (OR, 0.51) or had less education (OR, 0.37) were less likely to express willingness to have a telehealth appointment (10). Previous research shows that it is highly likely to have health disparities in non-metropolitan areas, and rural hospitals were less likely to use telehealth systems, such as checking patients' health information online (11).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the telephone, specific telemedical apps/tools are only rarely used to communicate with a doctor in Austria, and are therefore not (yet) relevant. This contrasts with the situation, for example, in the United States, where a recent study encompassing 2555 respondents revealed that 50.8% of them used a non-telephone telehealth modality, including 31.9% making use of patient portals and 4.2% of videoconferencing tools [ 27 ]. On the background of the lower popularity of more specialized telehealth tools in Austria, taking a “modern approach” just for the sake of being modern apparently seems unimportant, with only 1.4% of respondents who had received and were content with their telemedical care saying they were satisfied because of the modern approach ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Between mid-March and early May 2020, telehealth was used by over 40% of patients with a chronic physical health condition (including almost 14% having done so by video) and over 50% of those with a behavioral health condition (30% by video) or seeking care for a new health condition (21% by video). A 2019 ALP study found that less than 4% of Americans had a video telehealth visit in the past year 6 .…”
Section: Discussionmentioning
confidence: 99%